Politics of minority educational institutions: Law and reality in the subcontinent - "Mahmood, Tahir(ed.)" (Gurgaon, 2007)
The right of the minorities to establish and administer educational institutions of their choice guaranteed by the Constitution of India has from the very beginning been entangled in a labyrinth of political vicissitudes and changing in judicial attitudes. The resulting uncertainties in this matter have had the effect of perpetuating tremendous inequalities in respect of literacy and education between various sections of the Indian citizenry. This anthology examines in depth the constantly changing rulebook and the persisting realities relating to the educational rights and institutions of the minorities. Having its focus on India, with a view to providing a comparative perspective it includes some articles and inputs on trends in Pakistan, Bangladesh, ,UK and USA.
Keywords: Educational rights-Minority